PENGARUH MODEL PROBLEM BASED LEARNING PADA PEMBELAJARAN BIOLOGI TERHADAP KEMAMPUAN LITERASI SAINS SISWASMA - Aradia, Fani Fenty; Helendra; Fuadiyah, Sa'diatul; Anggiyani, Ria (Universitas Cokroaminoto Palopo, 2024)
21st century education aims to improve students' scientific literacy skills. The results of the PISA study show that Indonesian students' scientific literacy is in the low category. The low level of student scientific literacy is caused by several factors in the education system, such as the curriculum, teachers and students themselves. This research aims to see the effect of the model Problem Based Learning (PBL) in Biology learning on students' scientific literacy abilities at SMAN 2 Pulau Punjung based on three aspects of scientific literacy, namely aspects of context, knowledge and competence. This research is experimental research with methods like an experiment. The research sample consisted of 70 students consisting of two classes taken using engineering purposive sampling. The instrument used is a scientific literacy test. The data analysis techniques used are divided into three, namely normality test, homogeneity test and hypothesis test. Based on the research results, it is known that the hypothesis test results obtained were 0.000 < 0.05. This shows that there is an influence of the PBL model on students' scientific literacy abilities in Biology learning at SMAN 2 Pulau Punjung. This can be seen in the average value of the scientific literacy abilities of students taught using the PBL model which is higher than the average scientific literacy abilities of students taught using the learning model. discovery learning